Video-Assisted Thoracic Surgery vs. Thoracotomy for the Treatment in Patients With Esophageal Leiomyoma: A Systematic Review and Meta-Analysis - Shen, Cheng; Li, Jue; Che, Guowei (Frontiers in Surgery, 2022)
Background: Surgical treatment is usually suitable for patients with esophageal leiomyoma. Video-assisted thoracic surgery (VATS) offer a minimally invasive approach to thoracotomy. However, there is no clear conclusion whether VATS can achieve an equal or even better surgical effect when compared with traditional open approach in treatment of esophageal leiomyoma. We performed this meta-analysis to explore and compare the outcomes of VATS versus thoracotomy for patients with esophageal leiomyoma. Methods: PubMed, Cochrane Library, EMBASE, China National Knowledge Infrastructure (CNKI), Medline, and Web of Science databases were searched for full-text literature citations. The quality of the articles was evaluated using the Newcastle-Ottawa Scale (NOS) and the data analyzed using the Review Manager 5.3 software. Fixed or random effect models were applied according to heterogeneity. Results: A total of 8 studies with 290 patients, of whom 141 patients were in the VATS group and 149 in the thoracotomy group, were involved in the analysis. Compared with thoracotomy, VATS was associated with shorter operative time, less blood loss in operation and shorter postoperative hospital stay. There is no significant difference in postoperative pleural drainage day and postoperative complications between the two groups. Conclusions: VATS has more advantages over thoracotomy, indicating that VATS is better than thoracotomy in terms of postoperative recovery. We look forward to more large-sample, high-quality studies published in the future.